A Functional Programming Language in Tamil: The Use Of Native Language for Programming - Hemavathi, S.; Jayasakthi velmurugan, K. (International Journal of Engineering and Technology, 2018)
Learning a new programming language has always been a daunting task for the students who feel difficult to understand the program. Most of the programming languages that are used for teaching purpose is present in English language. Learning in mother tongue is enjoyable and thus create technically sound citizens for the development of society which increases the learning curve. The purpose of this work is to create a programming language which uses Tamil characters to create programs with current technology. The goal is to make programming easier for students whose native language is Tamil. The system will provide all the necessary tools for learners to create programs and understanding the concepts which are widespread among the available languages. It includes all the phases of compiler along with the creation of set of keywords. The system can be implemented by creating an interpreter that will run the code and will execute on console like all widely used programming languages. It will implement concepts that are rudimentary basics which are present in other programming languages. User can interact with the interpreter either using a REPL (Read Evaluate Print Loop) or by writing the program in a text-file and run it using the command line argument. The interpreter will be available as an installable package for running the program. Thus, students can learn programming easier in their native language and get exposed to the concepts of programming which can be enhanced for future technologies.Â Â